Pengaruh Konseling Kelompok Terhadap Motivasi Belajar Siswa SMA Al-Atiqiyah Cipanengah Sukabumi - Nenden Sri Haryati; Zahra Isnaini; Diandi Nurhakim (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2021)
The purpose of this study was to find out how much influence group counseling has on motivation to study at Al-Atiqiyah Cipanengah Sukabumi High School. This study uses quantitative methods with product momentdata analysis techniques, and data collection techniques using closed questionnaires in which there are alternative answers that have been determined by researchers. The sample in the study was 29 teachers, and 30 students. From the results of the analysis of student questionnaire data using the product moment correlation formula obtained Υwork 0.727. After consultation with the critical price table at n 30 with significant levels of 95% 0.361 and 99% 0.463. then from the results of the teacher questionnaire data obtained work 1.32. After being consulted with the critical price table at n 29 with a significant level of 95% 0.367 and 99% 0.470 came to the conclusion that there is an influence of group counseling on the learning motivation of Al-Atiqiyah Cipanengah Sukabumi High School students with a significant high level Υ.